TGFβ3, dibutyryl cAMP and a notch inhibitor modulate phenotype late in stem cell-derived dopaminergic neuron maturation - Sibuea, Shanti; Ho, Joan K.; Pouton, Colin W.; Haynes, John M. (Frontiers in Cell and Developmental Biology, 2023)
The generation of midbrain dopaminergic neurons (mDAs) from pluripotent stem cells (hPSC) holds much promise for both disease modelling studies and as a cell therapy for Parkinson’s disease (PD). Generally, dopaminergic neuron differentiation paradigms rely on inhibition of smad signalling to induce neural induction followed by hedgehog signalling and an elevation of -catenin to drive dopaminergic differentiation. Post-patterning, differentiated dopaminergic neuron cultures are permitted some time for maturation after which the success of these differentiation paradigms is usually defined by expression of tyrosine hydroxylase (TH), the rate limiting enzyme in the synthesis of dopamine. However, during maturation, culture media is often supplemented with additives to promote neuron survival an or promote cell differentiation. These additives include dibutyryl cyclic adenosine monophosphate (dbcAMP), transforming growth factor β3 (TGFβ3) and or the γ-secretase inhibitor (DAPT). While these factors are routinely added to cultures, their impact upon pluripotent stem cell-derived mDA phenotype is largely unclear. In this study, we investigate how the omission of dbcAMP, TGFβ3 or DAPT, late in maturation, affects the regulation of multiple dopaminergic neuron phenotype markers. We now show that the removal of dbcAMP or TGFβ3 significantly and distinctly impacts multiple markers of the mDA phenotype (FOXA2, EN1, EN2, FOXA2, SOX6), while commonly increasing both MSX2 and NEUROD1 and reducing expression of both TH and WNT5A. While removing DAPT produced significant impacts upon MSX2, OTX2, EN1 and KCNJ6. In the absence of any stressful stimuli, we suggest that these culture additives should be viewed as mDA phenotype-promoting, rather than neuroprotective. We also suggest that their addition to cultures is likely to confound results of both transplantation and disease modelling studies.